2010
DOI: 10.1172/jci40778
|View full text |Cite
|
Sign up to set email alerts
|

Shank-interacting protein–like 1 promotes tumorigenesis via PTEN inhibition in human tumor cells

Abstract: Inactivation of phosphatase and tensin homolog (PTEN) is IntroductionWhile PTEN displays phosphatase activity for both protein and lipid substrates (1), accumulating evidence reveals that its lipid phosphatase activity, which dephosphorylates the 3ʹ-position phosphate from the inositol ring of phosphatidylinositol 3,4,5-triphosphate (PIP 3 ) (2, 3), contributes to PTEN's tumor suppression activities. Thus, PTEN directly antagonizes a critical oncogenic activity mediated by PI3K (4, 5).Consistent with its bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 64 publications
7
97
0
1
Order By: Relevance
“…In addition, RNAi-mediated knockdown or overexpression of P-Rex2a was also able to control xenograft tumor formation in vivo (36). The evidence of cancer xenograft models in our study has already been shown, but studies to date have shown only changes in tumor size when cells were transfected by miR-338-3p and control vector, and then injected to produce the tumor model.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, RNAi-mediated knockdown or overexpression of P-Rex2a was also able to control xenograft tumor formation in vivo (36). The evidence of cancer xenograft models in our study has already been shown, but studies to date have shown only changes in tumor size when cells were transfected by miR-338-3p and control vector, and then injected to produce the tumor model.…”
Section: Discussionsupporting
confidence: 68%
“…SHARPIN is also amplified and upregulated in invasive ductal breast cancers [23] . SHARPIN expression was shown to be correlated with Akt activation, consistent with the abovementioned role of SHARPIN in inhibition of PTEN activity [15] . In prostate cancer, upregulated SHARPIN expression induces activation of the NF-κB pathway and its downstream targets Survivin and Livin [24] , which potentially inhibits apoptosis and contributes to tumor development.…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrsupporting
confidence: 75%
“…SHARPIN may facilitate tumorigenesis either by interacting with PTEN through its UBL domain to inhibit its phosphatidylinositol 3,4,5-trisphosphate phosphatase activity [15] or by decreasing PTEN expression [16] . SHARPIN also acts as an endogenous inhibitor of integrin signaling [17] .…”
Section: Research Highlightmentioning
confidence: 99%
“…P-Rex2 and SIPL1 bind to PTEN directly and inhibit its lipid phosphatase activity. 64,65 Both of these proteins can stimulate cell growth, at least in part, through their effects on PTEN. P-Rex2a inhibits PTEN lipid phosphatase activity and stimulates the PI3K pathway in the presence of PTEN, whereas knockdown of SIPL1 reduces cell growth in the presence and absence of PTEN, indicating that SIPL1 has other targets besides PTEN.…”
Section: Pseudo-pten and Other Oncogenes Decoys For Mirnasmentioning
confidence: 99%